Prevalence, clinical outcomes and rainfall association of acute respiratory infection by human metapneumovirus in children in Bogotá, Colombia (2019)
Background: Acute respiratory infections (ARIs) are one of the main causes of morbidity and mortality in children. Viruses are the main etiological agents, and their behavior tends to be seasonal and vary by geographical location. Human metapneumovirus (HMPV) has recently been described as a cause of severe acute respiratory infection and its prevalence and clinical behavior in children at moderate altitudes is unknown. Methods: A cross-sectional study was carried out on patients seen at a university hospital in Bogotá, Colombia between October 2015 and December 2017 in a city at a moderate altitude above sea level. Children with acute respiratory infections who had had a multiplex RT-PCR assay were selected. The prevalence of HMPV infection, its clinical outcomes and its relationship to rainfall were evaluated. Results: Out of a total of 14,760 discharged patients, multiplex RT-PCR was performed on 502 and a virus was detected in 420 children with acute respiratory infection (ARI). The study group had a median age of 21 months (IQR 7-60), with similar proportion of males and females (56.4 and 43.6% respectively) and 5.2% (CI 95 3.3-7.8%) prevalence of HMPV infection. The group with HMPV infection showed a greater frequency of viral coinfection (22.7% vs 14% P = 0.03) compared with ARI caused by other viruses. The rate of bacterial coinfection (P = 0.31), presence of comorbidities (p = 0.75), length of hospital stay (P = 0.42), need for mechanical ventilation (P = 0.75) and mortality (P = 0.22) were similar for HMPV and other viral infections. A moderate correlation was established between HMPV infection and rainfall peaks (Spearman's Rho 0.44 p = 0.02). Conclusions: Human metapneumovirus was the fifth most frequently isolated virus in children with ARI, had similar clinical behavior and severity to other viruses but a higher rate of viral coinfection. Its peaks seem to correlate to rainy seasons. © 2019 The Author(s).